Penggunaan Media Pembelajaran Teka-teki Silang Online untuk Meningkatkan Kemampuan Menyusun Kalimat Majemuk - Kuncara, Kusuma Peny; Farikah; Mulyani, Mimi (Kajian Bahasa dan Sastra (KABASTRA), 2021)
This conceptual article describes the use of online crossword puzzle learning media to improve the ability to compose compound sentences. Online crossword puzzle learning media can be used as an alternative in varying the learning media. The existence of innovative and appropriate learning variations can help to achieve learning objectives and improve student achievement. The use of online crossword puzzle learning media also has various advantages. There are seven advantages of using online crossword puzzle learning media, namely, 1) learner-centred learning, 2) students become creative and think critically, 3) students can solve problems, 4) varied and interesting learning media, 5) students become motivated, 6) increase student achievement, and 7) can be accessed anywhere. In addition, the online crossword puzzle learning media is very effective in learning to compose compound sentences. Making crosswords online for learning to compose compound sentences is very easy, you only need to go through a few steps. Making crosswords online using the Eclipse Crossword Puzzle application and the LIVEWORKSHEETS webpage. It is also easy to apply the results from the Eclipse Crossword Puzzle application and the LIVEWORKSHEETS webpage. Just need to share the link from the LIVEWORKSHEETS webpage with students. Students can also easily access the link via smartphones, laptops, or PCs that are connected to the internet.